2021
DOI: 10.1177/0271678x211065924
|View full text |Cite
|
Sign up to set email alerts
|

Trans-cerebral HCO3 and PCO2 exchange during acute respiratory acidosis and exercise-induced metabolic acidosis in humans

Abstract: This study investigated trans-cerebral internal jugular venous-arterial bicarbonate ([HCO3−]) and carbon dioxide tension (PCO2) exchange utilizing two separate interventions to induce acidosis: 1) acute respiratory acidosis via elevations in arterial PCO2 (PaCO2) (n = 39); and 2) metabolic acidosis via incremental cycling exercise to exhaustion (n = 24). During respiratory acidosis, arterial [HCO3−] increased by 0.15 ± 0.05 mmol ⋅ l−1 per mmHg elevation in PaCO2 across a wide physiological range (35 to 60 mmHg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 108 publications
1
8
0
Order By: Relevance
“…For example, during hyperoxic rebreathing techniques, the central chemoreflex threshold is ∼40–42 Torr (e.g., Boulet et al., 2016; Duffin & McAvoy, 1988), at which the end‐tidal values are likely to approximate brainstem tissue levels (e.g., Boulet et al., 2016; Casey et al., 1987). However, this feature is not the case when breathing ambient air or fixed fractional increases in CO 2 , because the usual arrangement is that of the steady state, where any measured end‐tidal CO 2 value is likely to be 6–8 Torr lower than tissue values (e.g., Caldwell et al., 2022). Thus, when interpreting a VRT of ∼40 Torr CO 2 from experiments using rebreathing techniques, it is difficult to make comparisons to experiments using steady‐state techniques (i.e., the present study).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, during hyperoxic rebreathing techniques, the central chemoreflex threshold is ∼40–42 Torr (e.g., Boulet et al., 2016; Duffin & McAvoy, 1988), at which the end‐tidal values are likely to approximate brainstem tissue levels (e.g., Boulet et al., 2016; Casey et al., 1987). However, this feature is not the case when breathing ambient air or fixed fractional increases in CO 2 , because the usual arrangement is that of the steady state, where any measured end‐tidal CO 2 value is likely to be 6–8 Torr lower than tissue values (e.g., Caldwell et al., 2022). Thus, when interpreting a VRT of ∼40 Torr CO 2 from experiments using rebreathing techniques, it is difficult to make comparisons to experiments using steady‐state techniques (i.e., the present study).…”
Section: Discussionmentioning
confidence: 99%
“…However, this feature is not the case when breathing ambient air or fixed fractional increases in CO 2 , because the usual arrangement is that of the steady state, where any measured end-tidal CO 2 value is likely to be 6-8 Torr lower than tissue values (e.g., Caldwell et al, 2022).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…By contrast, during ETF, the within‐individuals P jv‐a CO 2 appears less variable than with rebreathing, but the mean P jv‐a CO 2 decreases at each stage, probably as a result of the influence of CVR. This produces a relatively predictable stage‐wise decrease in P jv‐a CO 2 because of the steady‐state nature of each PaCnormalO2${P_{{\mathrm{aC}}{{\mathrm{O}}_{\mathrm{2}}}}}$stage (Caldwell et al., 2021). This difference between methods could be the result of normal between‐individual physiological variability in the rate of rise of the relevant parameters (PaCnormalO2${P_{{\mathrm{aC}}{{\mathrm{O}}_{\mathrm{2}}}}}$, P jv CO 2 and/or CBF), or the result of the dynamic nature of the PaCnormalO2${P_{{\mathrm{aC}}{{\mathrm{O}}_{\mathrm{2}}}}}$ ramp during rebreathing increasing the technical variability involved in simultaneous arterial and jugular venous blood draws.…”
Section: Discussionmentioning
confidence: 99%
“…This narrowing is likely attributable to increases in [HCO 3 -] and CO 2 'wash-out' due to higher CBF with hypercapnia; for example, the venous-arterial HCO 3 and CO 2 differences were each related to increases in CBF (both P < 0.001). Data are from Caldwell et al (2021a).…”
Section: Acute Alterations In Cerebral Blood Flow Stabilize Comentioning
confidence: 99%
“…6) – a change likely attributable to increased intracellular HCO 3 – ‘wash‐out’ as the reduction in trans‐cerebral [HCO 3 – ] difference is related to the hypercapnic CBF response (Caldwell et al . 2021 a ). Arvidsson and colleagues (1981) showed that intravenous infusion of NaHCO 3 in hypercapnic dogs causes a 50−70% reduction in CBF (from hypercapnic elevation) paralleled by a reduction in arterial–venous O 2 difference such that CMnormalRO2 was unaltered.…”
Section: Introduction To Acid–base Physiologymentioning
confidence: 99%